Exploring the Influence of Age, Gender, and Occupation on Sleep-Related Habits and Perceptions - Krish Patel; Rudra Patel; Jenil Desai; Meet Satasiya; Rahul Chauhan; Andino Maseleno (International Journal of Psychology and Health Science, 2023)
This study investigates the relationship between demographic factors—specifically gender and occupation—and various sleep-related behaviors and perceptions among participants. Utilizing ANOVA analysis, significant differences were found regarding diagnosed sleep disorders based on gender, while occupational groups exhibited varied beliefs about the impact of sleep on physical health. The findings underscore the importance of targeted interventions and awareness campaigns tailored to specific demographic groups. Future research should explore the longitudinal effects of these factors and consider diverse populations to enhance generalizability. The global implications of sleep health are profound, influencing mental well-being, chronic disease prevalence, and workplace productivity. By prioritizing sleep as a critical component of health strategies, stakeholders can foster healthier communities and improve overall quality of life.